The Black Power Movement: A historiographical understanding of how scholarship has shaped the legacy of the Black Power Movement - Robert Lynn (Cogent Arts & Humanities, 2023)
AbstractScholarship surrounding the Black Power Movement has shifted from the previous century to articulate a new perspective conducive to the realities of the past. Similarly, contemporary scholars have become the conduit of Black Power’s revolutionary violence. This illustrates the Black Power Movement as a more significant movement, leaving behind legacies and beliefs that transpired into modern-day protest tactics. Additionally, Contemporary scholarship, by being aware of historical writing, has expanded the production of history through the lenses of race, gender, class, and power. Such categories have been used as an analytical lens to interpret the past and correctly characterize the legacies of various Black Power Movement organizations and people, unlike in the previous century. Contemporary scholarship has made it clear that the legacy of the Black Power Movement has played a role in constructing modern-day literature and perspectives.